Storied reflections: Development of a longitudinal interdisciplinary curriculum to improve patient-provider communication - Nicole Defenbaugh, PhD; Lorraine A. Dickey, MD, MBA; Vivian C. Foulke, RNC, BSN; James P. Orlando, EdD (Elsevier, 2023)
Objective: This article details the development of an interdisciplinary graduate medical education (GME) narrative curriculum. Methods: Descriptive statistics were conducted for the narrative session surveys. Two separate qualitative analyses were conducted. First, content and thematic analyses of the open-ended questions in the survey using NVIVO software occurred. Second, an inductive analysis of the participants' 54 stories was performed to identify unique themes not related to the prompt topics. Results: Quantitative survey results demonstrated that 84% of learners' felt the session benefited their personal or professional sense of wellbeing and resilience, 90% of learners believed the sessions aided in their ability to listen more effectively, and 86% of learners could apply what they practiced or witnessed. Qualitative analysis of survey data showed learners focused on patient care and listening. Thematic analysis of participants' narratives revealed strong feelings and emotions, struggles with time management, increase in self- and other-awareness, and challenges managing job-life balance. Conclusion: The longitudinal interdisciplinary Write-Read-Reflect narrative exchange curriculum is cost-effective, sustainable, and demonstrably valuable to learners and their program directors across multiple disciplines. Innovation: The program was designed for 4 graduate programs' learners to simultaneously experience a narrative exchange model to improve patient-provider communication, support professional resilience, and deepen relationship-centered care skills.